2019
DOI: 10.3844/ajisp.2019.5.9
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Extremely Biodiverse Probiotic and a Supplement Based on Microbial Chondroitin Sulfate is Associated with a Significant Decrease of Serum Free Kappa Light Chains as well as a Trend Toward Normalization of Kappa/Lambda Ratio and of Plasma Cell Bone Marrow Infiltration in a Case of Multiple Myeloma

Abstract: We describe the case of a 71-year-old woman with multiple myeloma associated with severe chronic renal insufficiency who, since October 2018, assumed a novel, extremely biodiverse, probiotic and a supplement based on microbial chondroitin sulfate, vitamin D 3 and ultrapure phosphatidylcholine; such a nutritional regimen was associated with a dramatic decrease of serum free Kappa light chains (from 2,190 to a minimum of 119.40 mg/L) as well as a trend toward normalization of Kappa/Lambda ratio (from 187 to a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 15 publications
6
11
0
Order By: Relevance
“…Not surprisingly, human RAD52, an evolutionary derivative of Sak, was recently defined "a novel player in DNA repair in cancer and immunodeficiency" and was attributed a tumor suppressor function (45). These functions of Sak/RAD52 are consistent with a recent clinical observation in a case of multiple myeloma (19). It is also worth noticing that RAD52 was demonstrated to suppress HIV-1 infection in a manner independent of its ability to repair DNA double strand breaks through homologous recombination (46).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Not surprisingly, human RAD52, an evolutionary derivative of Sak, was recently defined "a novel player in DNA repair in cancer and immunodeficiency" and was attributed a tumor suppressor function (45). These functions of Sak/RAD52 are consistent with a recent clinical observation in a case of multiple myeloma (19). It is also worth noticing that RAD52 was demonstrated to suppress HIV-1 infection in a manner independent of its ability to repair DNA double strand breaks through homologous recombination (46).…”
Section: Discussionsupporting
confidence: 64%
“…After 48 hrs, the product undergoes the process of freeze drying. The nutritional characteristics of the product are described in Antonucci et al (2019) (19). The array used for this analysis is a chip covered in short DNA sequences that are specific to certain target organisms (a total of approximately 12,000 species are included).…”
Section: Methodsmentioning
confidence: 99%
“…The experience of the subject suggests that the consumption of an extremely biodiverse probiotic yogurt described in references 1 and 2 is associated increased urinary excretion of toxicants, modulation of the immune system, and rebalance of the gut microbiota with overall positive effects on health. The authors wish to emphasize that the data in this case report are from one individual, and not part of a larger study even though they confirm and expand the results observed in other, unrelated, articles (3)(4)(5)(6).…”
Section: Discussionsupporting
confidence: 81%
“…We have previously observed and reported in two recent articles (1,2) that the consumption of an extremely biodiverse probiotic yogurt with a unique microbial composition is associated with detoxification of non-metal toxicants (3), decrease of serum alpha-Nacetylgalactosaminidase (nagalase) activity (3,4), decrease of serum C-reactive protein (CRP) (4), decrease of markers specific for multiple myeloma (5), and a dramatic decrease of viral load in Hepatitis B (6).…”
Section: Introductionmentioning
confidence: 99%
“…The unique microbial composition of this probiotic blend was fully described in two recent articles (30,31). Human consumption of this blend is associated with detoxification of non-metal toxicants (32), decrease of serum alpha-N-acetylgalactosaminidase (nagalase) activity (32,33), decrease of serum C-reactive protein (CRP) (33), decrease of markers specific for multiple myeloma (34), and decrease of viral load in Hepatitis B (35).…”
Section: Methodsmentioning
confidence: 99%